Osteoarticular pain and depression in older adults treated in a geriatric hospital in Lima, Peru - Maceda Limo, Pamela (2022)
Objective: To determine the relationship between osteoarticular pain and depression in older adults treated in a geriatric hospital in Lima, Peru. Materials and methods: An observational and descriptive study. A sample of 74 older adults treated in the outpatient department of a geriatric hospital in Lima, Peru, in 2021 was selected. A survey was used as technique and a questionnaire as instrument. Using the IBM SPSS Statistics statistical software, a chi-square test was performed with a significance level of 5 %. Results: Concerning the older adults’ general characteristics, 51.35 % were over 70 years of age, 55.41 % were women, 60.81 % had secondary education and 86.49 % were married or cohabiting. Regarding the characteristics of pain, 32.43 % stated that the pain decreased when they were not alone, 20.27 % pointed out that the pain was more intense at home, 81.08 % had moderate pain and 64.86 % had experienced pain for more than six months. As for depression, 43.24 % dealt with mild depression and 29.73 % had persistent depression. The characteristics of osteoarticular pain associated with depression were the degree of pain (p = 0.041) and duration of pain (p = 0.024). Conclusions: Osteoarticular pain was significantly associated with depression in older adults treated in a geriatric hospital in Lima, Peru.